Managing Cognitive Resources in Post-Combat Trauma Recovery: A Neuropsychological Assessment Based on Eye-Tracking Metrics - Солонський, Андрій; Danylov Сергій (Psychosomatic Medicine and General Practice, 2024)
In this abstract, we propose examining the use of neuropsychological assessment of attention based on webcam-based eye-tracking technology as indicators of cognitive resources in soldiers. Without diminishing the importance of mild traumatic brain injuries and other physical and psychological traumas, we suggest looking at the recovery process through the lens of dynamic resource allocation mechanisms. Highlighting the results of a pilot study conducted at "Feofaniya" Hospital, we present hypotheses regarding the factors that contribute to the recovery of military personnel.